The comparison of flexibility, muscle strength, coordination and balance between children involve in swimming and active children / Mohd Akram Mustaqim Mohd Zamani - Mohd Zamani, Mohd Akram Mustaqim (Faculty of Sport Science and Recreation, 2017)
The purpose of this study was to compare the flexibility, strength, coordination and balance between children involve in swimming and active children. These studies are to know that activity like swimming can improve children ability or not. Children who involve in swimming which is from swimming club and active children is the kindergarten child who are not involve in swimming. A total forty children (N=40) divided by 2 group which is 20 come from swimming club children and another 20 come from kindergarten. The age of this children are around 4 to 6 years old only. This study was using one test for each of the ability. Using sit and reach test for flexibility, chair push up for strength, ball toes wall test for coordination and flamingo balance test for balance. At the end on this study showed, there is the advantage of swimming toward flexibility, strength, coordination and balance. The null hypothesis is rejected. The result of flexibility is (.000), strength (.007), coordination (.013) and last is balance (.020) for significant 2 tailed. This result proved that there is, the significant between swimming children and active children toward flexibility, strength, coordination and balance. Based on these result, children must involve in swimming and at the same time there will use their leisure time for good activity. In future study, separate the group by gender to know the difference between male and female children. As a conclusion, the swimming activity for children in 4 to 6 years old had advantage of flexibility, strength, coordination and balance.